PARAMETRIC SYNTHESIS AND OPTIMIZATION OF THE PARAMETERS OF THE AERODYNAMIC GRIPPER OF CUT DETAILS FROM THE STACK OF TEXTILE FOR AUTOMATED SEWING MACHINES LOADING - МІСЯЦЬ, МИХАЙЛО; ОРЛОВСЬКИЙ, БРОНІСЛАВ (Technologies and Engineering, 2024)
Goal. Automation of loading sewing machines with cut parts on the basis of parametric synthesis in order to optimize the process of individual separation of cut parts from a pack by the aerodynamic grabber of a sewing manipulator and to determine the most rational combination of parameters that characterize the criterion for optimizing the basing of textile cut parts relative to their center of mass and one of the design parameters of the aerodynamic sewing manipulator gripper plates. The methodology. In order to optimize the process of individual separation of cut textile parts from a bundle, the method of planning theory and analysis of a multi-factor experiment was applied for the proposed generalized indicator of the quality of constructed experimental-statistical models and to determine the extreme values of the parameters of the individual separation process using the aerodynamic method and the dyad device "sewing manipulator grabber – textile cut detail" with the most rational combination of significant parameters. Result. To optimize the process of piece-by-piece separation of textile cut parts from a bundle with an aerodynamic gripper, an experimental setup was developed and a numerical experiment was performed. Graphical nomograms of two-dimensional cross-sections of the response surfaces of the target function for engineering calculations of design parameters and the work process of the aerodynamic gripper of the sewing manipulator for loading machines with cut parts from textiles of various groups of sewing products were constructed. Graphical interpretation and numerical calculations of the obtained formulas and mathematical models were performed to optimize the process of individual separation of textile cut parts from a pack using an aerodynamic method and a device for designing a mechanical-technological pair "sewing manipulator gripper - textile cut part" with the most rational combination of parameters that characterize the process of basing textile cut parts relative to their center of mass and one of the design parameters of the aerodynamic plate of the sewing manipulator gripper. Scientific novelty: it consists in revealing the regularities of the optimization of the parameters of the aerodynamic grabber of textile cut parts from the stack for automated loading of sewing machines according to the results of the central rotatable composite plan of the 2nd order experiment (TsRKPE-2) at the adjusted zero levels of the controlled parameters , , mm and the realized 20x8 TsRKPE-2 matrix (20 series of experiments with 8 repetitions each). Statistical evaluations were carried out, which made it possible to obtain adequate 2nd-order mathematical models for the process of individual separation of textile cut parts from a stack for three optimization criteria , , – the duration of the cycle of individual separation from a stack of cut parts from shirt suit and coat group fabrics. Practical significance: a method of parametric synthesis was developed to determine the optimal parameters of the aerodynamic grabber and the cycle of individual separation of textile cut parts from the pile based on theoretical justification and experimental research of the interaction of the working environment with the cut parts of the shirt, coat and suit group.